(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article presents theoretical information about the role of play in the development of children, the importance of games in the development of a child’s personality, the inclusion of children in the game, as well as an analysis of its stages.